IMPLEMENTATION OF THE QUICK WINS PRESISI PROGRAM AT THE NORTH TAPANULI POLICE DEPARTMENT TO IMPROVE COMMUNITY SECURITY - Ernis Sitinjak; Rizkan Zulyadi; M. Citra Ramadhan (SOSIOEDUKASI, 2026)
This research to understand the implementation of the Quick Wins Presisi program at the North Tapanuli Police Department in enhancing community security through a qualitative approach using descriptive methods and a socio-legal perspective. The research explores the implementation process of the program, the obstacles and challenges encountered, as well as the community’s responses to the policing policy. Primary data were collected through in-depth interviews, field observations, and documentation involving police officers, community leaders, and local government officials. Meanwhile, secondary data were gathered from official documents, regulations, and relevant academic literature. Data analysis was conducted using Miles and Huberman’s interactive model, including data collection, reduction, presentation, and conclusion drawing, which was validated through source and method triangulation. The findings reveal that the implementation of the Quick Wins Presisi program at the North Tapanuli Police Department has positively contributed to increasing public trust and reducing crime rates in several areas, although it still faces challenges such as limited resources, inter-agency coordination, and social resistance. This research provides a comprehensive overview of the dynamics of police policy implementation at the regional level and offers strategic recommendations for strengthening the program based on participatory and socially responsive approaches.